Tunable channel spacing multiwavelength fiber laser based on semiconductor optical amplifier and Lyot filters - Muridan, Norasmahan (2021)
Requirements of high speed and vast data transmission capacity in fiber optic communication have led to the tunability enhancement of multiwavelength fiber laser (MWFL). Comparisons of MWFL performance based on different types of semiconductor optical amplifiers (SOAs) as the gain medium are rarely investigated. The achievement of channel spacing tunability by using a multi-segment Lyot filter based on SOA is also limited. This research focused on the generation of tunable channel spacing MWFL incorporating an SOA and advanced multi-segment Lyot filter. SOA offers several advantages such as lower mode competition and a wider wavelength bandwidth as compared to erbium-doped fiber amplifier. The unpredictable behavior of MWFL at different SOA, nonlinearity, and gain in the ring cavity leads to the investigation of multiwavelength spectra's performance based on linear SOA (LSOA), nonlinear SOA and booster optical amplifier utilizing a single Lyot filter. LSOA exhibits a flat and stable spectrum with 14 lasing lines within 3 dB bandwidth, extinction ratio (ER) of 42 dB, and peak power at -14.1 dBm. Later, a polarization-dependent isolator is added into the laser cavity, and the result showed an improvement in the overall laser performance for all SOAs. This is due to the intensity-dependent loss mechanism induced by the combination of SOA and polarizer. The LSOA is used for multiwavelength generation at different Lyot filter configurations as it outperforms other SOAs in terms of the number of lasing lines, ER, and the highest peak power. To achieve channel spacing tunability, the single Lyot filter is replaced with a parallel Lyot filter. A stable and tunable multiwavelength spectrum of up to three channels spacings is demonstrated for all the sets within the 10 dB bandwidth. The main novelty of this study is an advancement of the Lyot filter by adding another Lyot filter serially to the parallel Lyot filter to improve channel spacing tunability. Through polarization controllers’ adjustments, the channel spacing tunability has significantly improved and generated up to eight different channel spacings compared to only three used by previous researchers. The enhanced configuration of the Lyot filter with LSOA as the gain medium has a high potential in improving the performance of MWFL in channel spacing tunability for the wavelength division multiplexing system.